A polyarylether nitrile-based film material for flexible copper-clad laminate and a preparation method thereof
Polyarylethernitrile/silica and polyarylethernitrile/polytetrafluoroethylene composite films were prepared by nucleophilic substitution reaction and solution casting method, and the sandwich structure was constructed by hot pressing, which solved the existing flexible copper clad material media. The problems of insufficient electrical performance and debonding have achieved high peel strength, low dielectric loss and high tensile strength material properties.
Patent Information
- Application Number
- CN202411252607.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-09
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-09-09
AI Technical Summary
The existing flexible copper clad material has insufficient dielectric performance in high-frequency and high-speed applications, and the presence of adhesives leads to high dielectric loss and mismatch of thermal expansion coefficient, resulting in debonding and failure of electronic components.
Polyarylethernitrile polymers were synthesized by nucleophilic substitution reaction, and the polyarylethernitrile/silica composite film and polyarylethernitrile/polytetrafluoroethylene composite film were prepared by hot pressing. Film material for flexible copper clad plate.
The polyarylethernitrile-based film material for flexible copper clad plates with high peel strength, low dielectric loss and dielectric constant, low thermal expansion coefficient and high tensile strength is achieved, which improves the comprehensive performance of the material and is suitable for high-frequency and high-speed applications.
Smart Images

Figure CN118755127B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer material synthesis and processing technology, and specifically relates to a polyarylether nitrile-based film material for a flexible copper-clad laminate and a preparation method thereof. Background Art
[0002] Flexible copper clad laminate (FCCL) has the advantages of high wiring assembly density, light weight, small size, easy bending, high space utilization, and flexible process. Its main materials are adhesives, copper foil and resin. In recent years, researchers have mainly improved the thermal properties, electrical properties and bonding ability of flexible copper clad laminates by improving the performance or certain inherent parameters of adhesives, resin matrices and copper foils. The most common research is on the formulation parameters of adhesives, matrix resins and curing agents, which not only increases R&D costs, but also increases dielectric loss and dielectric constant due to the presence of adhesives, resulting in limited use in the field of high-frequency and high-speed copper clad laminates; most importantly, the mismatched thermal expansion coefficients of adhesives, matrix resins and copper foils will lead to debonding, causing electronic components to explode and fail. Therefore, it is necessary to develop a flexible copper clad laminate material that does not require adhesives.
[0003] As a special engineering plastic, polyarylethernitrile (PEN) not only has heat resistance, corrosion resistance, good processability and excellent mechanical properties. Specifically, the ether bond of its chain segment gives the polymer a certain toughness, the rigid benzene ring group gives the polymer a higher rigidity, and the polar group cyano gives the polymer good adhesion to metal without the need for adhesives. At the same time, the flexible molecular design gives it a certain crystallinity, and the cyano group gives it a cross-linking property, which is reflected in low hygroscopicity; the intrinsic low dielectric constant (3~5) and loss make the signal transmission loss of the flexible copper clad laminate low and have transmission stability.
[0004] The Chinese patent (CN115322417B, 2023-05-12) discloses a method for preparing a high modulus and high heat-resistant poly(arylethernitrile) self-reinforced film. Although the film has improved in thermodynamic and mechanical properties, it has not shown obvious advantages in dielectric properties. However, with the high frequency and high speed of terminal products, the requirements for the dielectric properties of flexible copper clad laminates are becoming increasingly urgent.
[0005] In view of the above problems, how to prepare polyarylether nitrile-based film materials for flexible copper-clad laminates with excellent comprehensive performance is a problem that technical personnel in this field urgently need to solve. Summary of the invention
[0006] The purpose of the present invention is to propose a method for preparing a polyarylether nitrile-based film material with high peel strength, low dielectric loss and dielectric constant, low thermal expansion coefficient and high tensile strength for a flexible copper clad laminate in view of the current problems. The polyarylether nitrile polymer is synthesized by a nucleophilic substitution reaction, a polyarylether nitrile / silicon dioxide composite film and a polyarylether nitrile / polytetrafluoroethylene composite film are prepared by combining a solution casting method, and a film material for a flexible copper clad laminate with a sandwich structure is prepared by hot pressing to improve the comprehensive performance of a substrate film for a flexible copper clad laminate. Finally, a polyarylether nitrile-based film material for a flexible copper clad laminate with high peel strength, low dielectric loss and dielectric constant, low thermal expansion coefficient and high tensile strength is obtained. The preparation process is simple, the effect is obvious, and it can be mass-produced and applied.
[0007] In order to solve the above technical problems, the present invention provides the following technical solutions:
[0008] A method for preparing a polyarylether nitrile-based film material for a flexible copper-clad laminate comprises the following steps:
[0009] Step 1, obtaining poly(arylene ether nitrile) powder:
[0010] Step 2, using the polyarylether nitrile powder and nano-silicon dioxide to prepare a polyarylether nitrile / silicon dioxide composite film S, and using the polyarylether nitrile powder and polytetrafluoroethylene powder to prepare a polyarylether nitrile / polytetrafluoroethylene composite film P;
[0011] Step 3: Prepare the polyarylether nitrile-based film material for flexible copper-clad laminate according to the stacking order of S / P / S.
[0012] Furthermore, step 2 specifically includes:
[0013] 2.1) The poly(arylether nitrile) powder and nano-silicon dioxide described in step 1 are added to solvent a and heated to react to obtain a poly(arylether nitrile) mixture hot solution B.
[0014] 2.2) Take the poly(arylene ether nitrile) powder and polytetrafluoroethylene powder described in step 1 and add them to solvent a for heating reaction to obtain a poly(arylene ether nitrile) mixture hot solution C.
[0015] 2.3) The mixed hot solution B and the mixed hot solution C are respectively formed into films by a tape casting method to obtain a poly(arylene ether nitrile) / silicon dioxide composite film S and a poly(arylene ether nitrile) / polytetrafluoroethylene composite film P, respectively.
[0016] Furthermore, step 3 specifically includes: taking the polyarylether nitrile / silicon dioxide composite film S and the polyarylether nitrile / polytetrafluoroethylene composite film P in step 2, stacking them in the order of S / P / S, copper-coating them on both sides, and hot pressing them to obtain a flexible copper-clad laminate, wherein the dielectric layer in the middle of the flexible copper-clad laminate is the polyarylether nitrile-based film material for the flexible copper-clad laminate.
[0017] Preferably, in step 2.1, the mass percentage of the nano-silicon dioxide in the polyarylethernitrile powder is 20%, and the particle size of the nano-silicon dioxide is 300 nm; in step 2.2, the mass percentage of the polytetrafluoroethylene powder in the polyarylethernitrile powder is 5% to 15%, and the particle size of the polytetrafluoroethylene powder is 1 to 15 microns.
[0018] Preferably, in step 2.1 or step 2.2, the solvent a is N-methylpyrrolidone; in step 2.1, the mass volume ratio of the polyarylethernitrile powder to the N-methylpyrrolidone is 1 g: 10-15 mL; in step 2.2, the mass volume ratio of the polyarylethernitrile powder to the N-methylpyrrolidone is 1 g: 10-15 mL.
[0019] Preferably, the reaction temperature of the heating reaction in step 2.1 and step 2.2 is both 200°C, the reaction time is both 2h, and the heating reaction is stirred; the heating process of the casting method in step 2.3 includes: the mixture hot solution B and the mixture hot solution C are kept warm at 80°C, 100°C, 120°C and 160°C for 1h respectively, and then kept warm at 200°C and 230°C for 2h respectively.
[0020] Preferably, the hot pressing in step 3 is performed at a temperature of 280-320° C., a time of 1 h-3 h, and a pressure of 8-10 MPa.
[0021] Preferably, in step 2.2, the mass percentage of the polytetrafluoroethylene powder to the poly(arylene ether nitrile) powder is 5% to 10%, and the particle size of the polytetrafluoroethylene powder is 1 micron.
[0022] More preferably, in step 2.2, the mass percentage of the polytetrafluoroethylene powder to the poly(arylene ether nitrile) powder is 5%, and the particle size of the polytetrafluoroethylene powder is 1 micron.
[0023] Unless otherwise specified, the above step 1 can use existing technology to prepare polyarylethernitrile powder, such as the technology for synthesizing hydroxyl-terminated polyarylethernitrile in step 1 in Chinese patent (CN115322417B, 2023-05-12).
[0024] The present invention also provides a polyarylether nitrile-based film material for a flexible copper-clad laminate, which is prepared by any of the above-mentioned preparation methods.
[0025] The above preparation methods all obtain polyarylether nitrile-based film materials for flexible copper-clad laminates with high peel strength, low dielectric loss and dielectric constant, low thermal expansion coefficient and high tensile strength.
[0026] Specifically, the mechanism of action of the polyarylether nitrile-based film material for preparing a flexible copper-clad laminate having high peel strength, low dielectric loss and dielectric constant, low thermal expansion coefficient, and high tensile strength is as follows:
[0027] First, the polyarylethernitrile is synthesized by nucleophilic substitution reaction, and the cyano group in the molecular chain segment is used as the site for bonding with the copper clad laminate. The temperature during high-temperature lamination causes a cross-linking reaction, which reduces the dielectric constant, enhances the rigidity of the film, and reduces the thermal expansion coefficient. Secondly, the filled nano-scale silica particles effectively improve the rigidity of the film material and reduce the thermal expansion coefficient in order to reduce the mismatch efficiency; the polyarylethernitrile / polytetrafluoroethylene alloy material is used to make the polymer film have lower dielectric loss, so that it has a better transmission effect when running in the high-frequency and high-speed direction; the addition of polytetrafluoroethylene powder improves the tensile strength of the film to a certain extent, and the selection of polytetrafluoroethylene particle size affects its dispersibility in the polyarylethernitrile resin and further affects the mechanical strength. Finally, the polyarylethernitrile / silicon dioxide composite film and the polyarylethernitrile / polytetrafluoroethylene composite film are laminated to form a sandwich structure, and the synergistic enhancement effect is used to enhance the peel strength and rigidity of the composite material in the flexible copper clad laminate substrate.
[0028] Therefore, it is very necessary to design a thin film material for flexible copper clad laminates with an organic-inorganic sandwich structure. The main body enhances the mechanical properties of the film and reduces the thermal expansion coefficient by compounding nanofiller particles, thereby reducing the probability of mismatch failure. Simultaneously, a polymer alloy material layer is constructed to regulate its dielectric properties and enhance the ability of dielectric transmission signals. The synergistic effect is used to create a "1+1>2" effect.
[0029] Compared with the prior art, the present invention has the following beneficial effects:
[0030] 1) The method for preparing a film material for a flexible copper clad laminate having a sandwich structure of the present invention improves the comprehensive performance of the substrate film for a flexible copper clad laminate through the synergistic enhancement effect of the polymer alloy material, and finally obtains a polyarylether nitrile-based film material for a flexible copper clad laminate having high peel strength, low dielectric loss, low thermal expansion coefficient, and high tensile strength.
[0031] 2) Compared with the polyarylethernitrile film material or polyarylethernitrile / silicon dioxide film material for flexible copper clad laminates, the dielectric constant and dielectric loss of the film material for flexible copper clad laminates with a sandwich structure prepared by the present invention are significantly reduced, indicating that the film material of the present invention has more advantages in meeting the dielectric requirements of high-frequency and high-speed product copper clad laminates.
[0032] 3) In the present invention, the poly(arylethernitrile) / polytetrafluoroethylene film formed by using micron-sized polytetrafluoroethylene and the poly(arylethernitrile) / silicon dioxide film formed by using nano-sized silicon dioxide play a synergistic role, further solving the problem of decreased tensile properties of the poly(arylethernitrile) film material for flexible copper clad laminates after adding silicon dioxide to form a composite film material.
[0033] 4) The preparation process of the present invention is simple, and the comprehensive performance of the obtained film material is significantly improved, which is conducive to large-scale production and application. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 It is a comparison chart of the peel strength of Examples 1 to 6 and Comparative Examples 1 to 2;
[0035] Figure 2 It is a comparison diagram of the linear thermal expansion coefficients of Examples 1 to 6 and Comparative Examples 1 to 2;
[0036] Figure 3 It is a comparison diagram of dielectric loss of Examples 1 to 6 and Comparative Examples 1 to 2;
[0037] Figure 4 It is a comparison chart of the tensile strength of Examples 1-6 and Comparative Examples 1-2. DETAILED DESCRIPTION
[0038] To make the purpose, technical solution and advantages of the present invention clearer, the present invention will be further described in detail below in conjunction with specific implementation methods and drawings. Unless otherwise specified, the reagents and materials used in the following examples and comparative examples are all commercially available products.
[0039] Example 1
[0040] This embodiment prepares a polyarylether nitrile-based film material for a flexible copper-clad laminate, and the preparation method includes the following steps:
[0041] Step 1, synthesis of poly(arylene ether nitrile):
[0042] 1.1 Add hydroquinone, biphenol and 2,6-dichlorobenzonitrile as reactants into a three-necked flask equipped with a thermometer, a water separator, a condensation reflux device and a mechanical stirring device, add potassium carbonate as a catalyst, and obtain a mixture powder; wherein the molar ratio of hydroquinone, biphenol, 2,6-dichlorobenzonitrile and potassium carbonate is 1:4.4:5:6; inject 15 mL of toluene and 15 mL of water into the water separator;
[0043] 1.2 Add the mixture powder obtained in step 1.1 into a mixed solvent of N-methylpyrrolidone (NMP) and toluene to obtain a mixed solution A; wherein 1.5 mL of the mixed solvent is added to every 1 g of the mixture powder, and the volume ratio of N-methylpyrrolidone (NMP) to toluene in the mixed solvent is 3:1;
[0044] 1.3 The mixed solution A obtained in step 1.2 was heated to 150°C at a heating rate of 5°C / min in an electric heating mantle, and reacted at 150°C for 2h; then the temperature was further increased to 170°C at a heating rate of 5°C / min, and reacted at 170°C for 1h; the water separator was opened to discharge 5mL of toluene within 3-5 seconds, and then the temperature was increased to 180°C at a heating rate of 10°C / min, and reacted at 180°C for 50min; finally, the temperature was lowered to 150°C, and the obtained reaction solution was poured into 0.2mol / L hydrochloric acid solution and stirred to obtain a strip solid A;
[0045] 1.4 The strip solid A obtained in step 1.3 is soaked in a 0.2 mol / L hydrochloric acid solution for 12 h, crushed, and then washed 3 to 5 times with boiling tap water until the solution is neutral; the washed powder is placed in a vacuum oven and dried for 12 h to obtain a white powder, which is poly(arylene ether nitrile).
[0046] Step 2, preparing poly(arylether nitrile) / silicon dioxide composite film, preparing poly(arylether nitrile) / polytetrafluoroethylene composite film:
[0047] 2.1 The poly(arylether nitrile) and nano-silica obtained in step 1 are added to N-methylpyrrolidone (NMP), and stirred at 200°C for 2h to obtain a poly(arylether nitrile) mixture hot solution B; wherein (10-15) mL N-methylpyrrolidone and 0.2 g nano-silica are added to every 1 g of poly(arylether nitrile) powder, that is, the mass ratio of poly(arylether nitrile) to nano-silica is 1:0.2; and the particle size of the nano-silica is 300 nm;
[0048] 2.2 The poly(arylether nitrile) and polytetrafluoroethylene obtained in step 1 are added to N-methylpyrrolidone (NMP), and stirred at 200°C for 2h to obtain a poly(arylether nitrile) mixture hot solution C; wherein (10-15) mL of N-methylpyrrolidone and 0.05 g of polytetrafluoroethylene are added to every 1 g of poly(arylether nitrile) powder, that is, the mass ratio of poly(arylether nitrile) to polytetrafluoroethylene is 1:0.05; the polytetrafluoroethylene is a powder, and the powder particle size is 1 micron;
[0049] 2.3 The mixed hot solution B and the mixed hot solution C obtained in steps 2.1 and 2.2 were respectively formed into films by tape casting to obtain poly(arylether nitrile) / silicon dioxide composite films and poly(arylether nitrile) / polytetrafluoroethylene composite films, respectively; wherein the heating process of the tape casting method is: keeping warm at 80°C, 100°C, 120°C and 160°C for 1 hour respectively, and then keeping warm at 200°C and 230°C for 2 hours respectively.
[0050] Step 3: Preparation of polyarylether nitrile-based film material for sandwich structure flexible copper-clad laminate:
[0051] The poly(arylether nitrile) / silicon dioxide composite film and the poly(arylether nitrile) / polytetrafluoroethylene composite film prepared in step 2.3 are stacked layer by layer in the order of (poly(arylether nitrile) / silicon dioxide)-(poly(arylether nitrile) / polytetrafluoroethylene)-(poly(arylether nitrile) / silicon dioxide), and copper-coated on both sides. After hot pressing, a flexible copper-clad laminate is obtained, and the middle dielectric layer is called a poly(arylether nitrile)-based film material for a flexible copper-clad laminate with a sandwich structure of (poly(arylether nitrile) / silicon dioxide)-(poly(arylether nitrile) / polytetrafluoroethylene)-(poly(arylether nitrile) / silicon dioxide), referred to as SPS composite film material. The hot pressing temperature is 280-320 °C, the time is 1 h-3 h, and the pressure is 8-10 MPa.
[0052] The performance of the SPS composite film material obtained in step 3 was measured, referring to the following standards: glass transition temperature according to GB / T 19466.2-2004, thermal decomposition temperature according to GB / T 27761-2011, dielectric constant and dielectric loss according to GB / T 31838.6-2021, peel strength according to GB / T 2792-2014, linear thermal expansion coefficient according to GB / T 36800.2-2018, tensile strength according to GB / T 1040.3-2006. The measuring methods of the film materials obtained in other embodiments and comparative examples are the same as those in Example 1.
[0053] The properties of the SPS composite film material obtained in Example 1 are as follows: glass transition temperature 208°C, thermal decomposition temperature 519°C, dielectric constant 3.90 (@1kHz), dielectric loss 0.012 (@1kHz), peel strength 10.82N / cm, linear thermal expansion coefficient 45.00×10 -6 (1 / K), film tensile strength 112 MPa.
[0054] Example 2
[0055] This embodiment prepares a poly(arylether nitrile)-based thin film material for a flexible copper-clad laminate. Compared with Embodiment 1, this embodiment differs in that: in step 2.2, the particle size of the added polytetrafluoroethylene powder is 15 microns; the rest of the preparation method is the same as that of Embodiment 1.
[0056] The properties of the SPS composite film material obtained in Example 2 are as follows: glass transition temperature 209 °C, thermal decomposition temperature 518 °C, dielectric constant 3.96 (@1kHz), dielectric loss 0.014 (@1kHz), peel strength 10.80 N / cm, linear thermal expansion coefficient 46.19×10 -6 (1 / K), film tensile strength 101 MPa.
[0057] Example 3
[0058] This embodiment prepares a poly(arylether nitrile) based thin film material for a flexible copper-clad laminate. Compared with the embodiment 1, this embodiment differs in that: in step 2.2, the particle size of the added polytetrafluoroethylene powder is 50 microns; the rest of the preparation method is the same as that of the embodiment 1.
[0059] The properties of the SPS composite film material obtained in Example 3 are as follows: glass transition temperature 209 °C, thermal decomposition temperature 519 °C, dielectric constant 4.03 (@1kHz), dielectric loss 0.017 (@1kHz), peel strength 10.78 N / cm, linear thermal expansion coefficient 47.25×10 -6 (1 / K), film tensile strength 85 MPa.
[0060] Example 4
[0061] This embodiment prepares a poly(arylether nitrile)-based thin film material for a flexible copper-clad laminate. Compared with Embodiment 1, this embodiment differs in that: in step 2.2, the mass of the added polytetrafluoroethylene is 10% of the poly(arylether nitrile), i.e., 0.1 g; the rest of the preparation method is the same as that of Embodiment 1.
[0062] The properties of the SPS composite film material obtained in Example 2 are as follows: glass transition temperature 209 °C, thermal decomposition temperature 519 °C, dielectric constant 3.75 (@1kHz), dielectric loss 0.011 (@1kHz), peel strength 10.85 N / cm, linear thermal expansion coefficient 47.99×10 -6 (1 / K), film tensile strength 103 MPa.
[0063] Example 5
[0064] This embodiment prepares a poly(arylether nitrile)-based thin film material for a flexible copper-clad laminate. Compared with Embodiment 1, this embodiment differs in that: in step 2.2, the mass of the added polytetrafluoroethylene is 15% of the poly(arylether nitrile), i.e., 0.15 g; the rest of the preparation method is the same as that of Embodiment 1.
[0065] The properties of the SPS composite film material obtained in Example 3 are as follows: glass transition temperature 210 °C, thermal decomposition temperature 514 °C, dielectric constant 3.30 (@1kHz), dielectric loss 0.010 (@1kHz), peel strength 10.02 N / cm, linear thermal expansion coefficient 48.38×10 -6 (1 / K), film tensile strength 99 MPa.
[0066] Example 6
[0067] This embodiment prepares a poly(arylether nitrile)-based thin film material for a flexible copper-clad laminate. Compared with Embodiment 1, this embodiment differs in that: in step 2.2, the mass of the added polytetrafluoroethylene is 20% of the poly(arylether nitrile), i.e., 0.20 g; and the rest of the preparation method is the same as that of Embodiment 1.
[0068] The properties of the SPS composite film material obtained in Example 3 are as follows: glass transition temperature 205 °C, thermal decomposition temperature 528 °C, dielectric constant 3.42 (@1kHz), dielectric loss 0.009 (@1kHz), peel strength 10.31 N / cm, linear thermal expansion coefficient 49.50×10 -6 (1 / K), film tensile strength 80 MPa.
[0069] Comparative Example 1
[0070] This comparative example prepares a polyarylethernitrile film material for a flexible copper-clad laminate, and the preparation method comprises the following steps:
[0071] Step 1, synthesis of poly(arylene ether nitrile):
[0072] 1.1 Add hydroquinone, biphenol and 2,6-dichlorobenzonitrile as reactants into a three-necked flask equipped with a thermometer, a water separator, a condensation reflux device and a mechanical stirring device, add potassium carbonate as a catalyst, and obtain a mixture powder; wherein the molar ratio of hydroquinone, biphenol, 2,6-dichlorobenzonitrile and potassium carbonate is 1:4.4:5:6; inject 15 mL of toluene and 15 mL of water into the water separator;
[0073] 1.2 Add the mixture powder obtained in step 1.1 into a mixed solvent of N-methylpyrrolidone (NMP) and toluene to obtain a mixed solution A; wherein 1.5 mL of the mixed solvent is added to every 1 g of the mixture powder, and the volume ratio of N-methylpyrrolidone (NMP) to toluene in the mixed solvent is 3:1;
[0074] 1.3 The mixed solution A obtained in step 1.2 was heated to 150°C at a heating rate of 5°C / min in an electric heating mantle, and reacted at 150°C for 2h; then the temperature was further increased to 170°C at a heating rate of 5°C / min, and reacted at 170°C for 1h; the water separator was opened to discharge 5mL of toluene within 3-5 seconds, and then the temperature was increased to 180°C at a heating rate of 10°C / min, and reacted at 180°C for 50min; finally, the temperature was lowered to 150°C, and the obtained reaction solution was poured into 0.2mol / L hydrochloric acid solution and stirred to obtain a strip solid A;
[0075] 1.4 The strip solid A obtained in step 1.3 is soaked in a 0.2 mol / L hydrochloric acid solution for 12 h, crushed, and then washed 3 to 5 times with boiling tap water until the solution is neutral; the washed powder is placed in a vacuum oven and dried for 12 h to obtain a white powder, which is poly(arylene ether nitrile).
[0076] Step 2: Preparation of poly(arylene ether nitrile) film:
[0077] 2.1 Add the poly(arylether nitrile) obtained in step 1 to N-methylpyrrolidone (NMP), stir and react at 200°C for 2h to obtain a hot solution of a poly(arylether nitrile) mixture; wherein (10-15) mL of N-methylpyrrolidone is added to every 1g of poly(arylether nitrile) powder;
[0078] 2.2 The hot solution of the mixture obtained in step 2.1 is formed into a film by a casting method to obtain a polyarylethernitrile film; wherein the heating process of the casting method is: keeping warm at 80°C, 100°C, 120°C and 160°C for 1 hour respectively, and then keeping warm at 200°C and 230°C for 2 hours respectively.
[0079] Step 3: Preparation of polyarylethernitrile film material for flexible copper clad laminate:
[0080] The polyarylethernitrile film prepared in step 2 is copper-clad on both sides and subjected to hot pressing treatment to obtain a polyarylethernitrile film material for a flexible copper-clad laminate; wherein the hot pressing temperature is 280-320°C, the time is 1 h-3 h, and the pressure is 8-10 MPa.
[0081] The performance of the polyarylethernitrile film material obtained in step 3 was measured in the same manner as in Example 1. The performance of the polyarylethernitrile film material obtained in Comparative Example 1 was as follows: glass transition temperature 214°C, thermal decomposition temperature 519°C, dielectric constant 4.15 (@1kHz), dielectric loss 0.020 (@1kHz), peel strength 7.42 N / cm, linear thermal expansion coefficient 52.38×10 -6 (1 / K), film tensile strength 102 MPa.
[0082] Comparative Example 2
[0083] This comparative example prepares a poly(arylether nitrile) / silicon dioxide thin film material for a flexible copper-clad laminate, and the preparation method comprises the following steps:
[0084] Step 1, synthesis of poly(arylene ether nitrile):
[0085] 1.1 Add hydroquinone, biphenol and 2,6-dichlorobenzonitrile as reactants into a three-necked flask equipped with a thermometer, a water separator, a condensation reflux device and a mechanical stirring device, add potassium carbonate as a catalyst, and obtain a mixture powder; wherein the molar ratio of hydroquinone, biphenol, 2,6-dichlorobenzonitrile and potassium carbonate is 1:4.4:5:6; inject 15 mL of toluene and 15 mL of water into the water separator;
[0086] 1.2 Add the mixture powder obtained in step 1.1 into a mixed solvent of N-methylpyrrolidone (NMP) and toluene to obtain a mixed solution A; wherein 1.5 mL of the mixed solvent is added to every 1 g of the mixture powder, and the volume ratio of N-methylpyrrolidone (NMP) to toluene in the mixed solvent is 3:1;
[0087] 1.3 The mixed solution A obtained in step 1.2 was heated to 150°C at a heating rate of 5°C / min in an electric heating mantle, and reacted at 150°C for 2h; then the temperature was further increased to 170°C at a heating rate of 5°C / min, and reacted at 170°C for 1h; the water separator was opened to discharge 5mL of toluene within 3-5 seconds, and then the temperature was increased to 180°C at a heating rate of 10°C / min, and reacted at 180°C for 50min; finally, the temperature was lowered to 150°C, and the obtained reaction solution was poured into 0.2mol / L hydrochloric acid solution and stirred to obtain a strip solid A;
[0088] 1.4 The strip solid A obtained in step 1.3 is soaked in a 0.2 mol / L hydrochloric acid solution for 12 h, crushed, and then washed 3 to 5 times with boiling tap water until the solution is neutral; the washed powder is placed in a vacuum oven and dried for 12 h to obtain a white powder, which is poly(arylene ether nitrile).
[0089] Step 2: Preparation of poly(arylene ether nitrile) / silicon dioxide composite film:
[0090] 2.1 The poly(arylether nitrile) and nano-silica obtained in step 1 are added to N-methylpyrrolidone (NMP), and stirred at 200°C for 2h to obtain a poly(arylether nitrile) mixture hot solution B; wherein (10-15) mL N-methylpyrrolidone and 0.2 g nano-silica are added to every 1 g of poly(arylether nitrile) powder, that is, the mass ratio of poly(arylether nitrile) to nano-silica is 1:0.2; and the particle size of the nano-silica is 300 nm;
[0091] 2.2 The mixed hot solution B obtained in step 2.1 was formed into a film by a casting method to obtain a poly(arylether nitrile) / silicon dioxide composite film; wherein the heating process of the casting method is: keeping warm at 80°C, 100°C, 120°C and 160°C for 1 hour each, and then keeping warm at 200°C and 230°C for 2 hours each.
[0092] Step 3: Preparation of poly(arylether nitrile) / silicon dioxide thin film material for flexible copper clad laminate:
[0093] The poly(arylether nitrile) / silicon dioxide composite film prepared in step 2 is copper-clad on both sides and subjected to hot pressing treatment to obtain a poly(arylether nitrile) / silicon dioxide film material for a flexible copper-clad laminate; wherein the hot pressing temperature is 280-320°C, the time is 1 h-3 h, and the pressure is 8-10 MPa.
[0094] The performance of the poly(arylether nitrile) / silicon dioxide film material obtained in step 3 was measured in the same manner as in Example 1. The performance of the poly(arylether nitrile) / silicon dioxide film material obtained in Comparative Example 2 was as follows: glass transition temperature 208°C, thermal decomposition temperature 521°C, dielectric constant 4.25 (@1kHz), dielectric loss 0.024 (@1kHz), peel strength 10.63 N / cm, linear thermal expansion coefficient 46.14×10 -6 (1 / K), film tensile strength 100 MPa.
[0095] In the performance measurement results of the film materials obtained in the above-mentioned Examples 1 to 6 and Comparative Examples 1 to 2, several key performance comparison diagrams are shown in FIG. Figures 1 to 4 The comparison results and analysis are as follows:
[0096] Figure 1 This is a comparison chart of peel strength. Figure 1 It can be seen that the peel strength of the polyarylether nitrile-based film material for flexible copper clad laminates of Examples 1 to 6 (all exceeding 10 N / cm) is significantly improved compared with Comparative Example 1 (7.42 N / cm), indicating that the polyarylether nitrile-based film material for flexible copper clad laminates of the present invention has a significant improvement in peel strength compared with the film for flexible copper clad laminates made of polyarylether nitrile itself. Among them, Examples 1 to 4 (not less than 10.78 N / cm) are also higher than Comparative Example 2 (10.63 N / cm), indicating that when the polyarylether nitrile-based film material for flexible copper clad laminates is prepared by the scheme of the present invention, when the mass of polytetrafluoroethylene added in the step of preparing the polyarylether nitrile / polytetrafluoroethylene composite film accounts for 5-10% of the polyarylether nitrile, the synergistic effect of polyarylether nitrile / polytetrafluoroethylene and polyarylether nitrile / silicon dioxide also improves the peel strength of the film material for flexible copper clad laminates prepared by using polyarylether nitrile / silicon dioxide alone.
[0097] The principle analysis is as follows: Peel strength refers to the maximum force required to peel the materials stuck together from the contact surface per unit width. The peeling angle is 180 degrees, and the unit is: Newton / cm (N / cm). It reflects the bonding strength of the material. The polar group cyano in the polyarylether nitrile matrix resin contributes strong polarity and has good adhesion to metallic copper. The film material of the present invention is laminated layer by layer, and the inorganic filler contributes rigidity, polytetrafluoroethylene contributes polar groups, and the bonding effect is synergistically increased. In particular, the addition of silicon dioxide improves the adhesion between polyarylether nitrile and copper foil. Therefore, the peel strength of the film material for the flexible copper-clad laminate constructed with a sandwich structure of the present invention is reflected as an enhanced effect.
[0098] Figure 2 is a comparison chart of linear thermal expansion coefficient. Figure 2 It can be seen that the linear thermal expansion coefficient of the polyarylethernitrile-based film material for the flexible copper-clad laminate of Examples 1 to 6 (all not higher than 50×10 -6 (1 / K)), compared with Comparative Example 1 (52.38×10 -6 (1 / K)) decreased to varying degrees, indicating that the polyarylethernitrile-based film material for flexible copper-clad laminates of the present invention has improved dimensional stability compared with the film for flexible copper-clad laminates made of polyarylethernitrile itself. -6 (1 / K) is also better than Comparative Example 2 (46.14×10 -6 (1 / K)), indicating that when the poly(arylether nitrile)-based thin film material for flexible copper clad laminates is prepared by the scheme of the present invention, when the polytetrafluoroethylene powder has a particle size of 1 micron and the mass of polytetrafluoroethylene added in the step of preparing the poly(arylether nitrile) / polytetrafluoroethylene composite film accounts for 5% of the poly(arylether nitrile), the synergistic effect of poly(arylether nitrile) / polytetrafluoroethylene and poly(arylether nitrile) / silicon dioxide further improves the dimensional stability of the thin film material for flexible copper clad laminates prepared by using only poly(arylether nitrile) / silicon dioxide.
[0099] The principle analysis is as follows: on the one hand, the polyarylethernitrile polymer itself has the property of cross-linking and can construct a rigid framework by forming a cross-linking network; on the other hand, the introduced silicon dioxide rigid particles can effectively strengthen the polymer matrix, so that the sandwich structure SPS film material constructed by the present invention has a lower linear thermal expansion coefficient.
[0100] Figure 3 is a comparison chart of dielectric loss. Figure 3It can be seen that the dielectric loss (0.024) of the film material of Comparative Example 2, which uses a polyarylether nitrile / silicon dioxide composite film to prepare a film material for a flexible copper clad laminate, is slightly inferior to that of Comparative Example 1 (0.020). The dielectric loss (all less than 0.017) of the polyarylether nitrile-based film material for a flexible copper clad laminate of Examples 1 to 6 is significantly reduced compared to Comparative Example 1 or Comparative Example 2, indicating that the polyarylether nitrile-based film material for a SPS flexible copper clad laminate of the present invention is more advantageous than the polyarylether nitrile film material for a flexible copper clad laminate and the film material after adding silicon dioxide to the composite film in meeting the dielectric requirements of a high-frequency and high-speed product copper clad laminate.
[0101] The principle analysis is as follows: by adding spherical silicon dioxide particles with low dielectric loss and polytetrafluoroethylene materials with excellent dielectric properties to construct a polymer alloy, and synchronously designing a sandwich structure, the dielectric loss can be effectively reduced. It can be seen that the polyarylether nitrile-based film material for flexible copper-clad laminates of the present invention has good high-frequency transmission efficiency; and the polytetrafluoroethylene powder with a particle size of 1 micron has a more superior dispersibility in the polyarylether nitrile matrix resin, so it is more conducive to improving its dielectric properties.
[0102] Figure 4 This is a comparison chart of tensile strength. Figure 4 It can be seen that the tensile strength (100 MPa) of the film material of Comparative Example 2, which uses a polyarylether nitrile / silicon dioxide composite film to prepare a film material for a flexible copper-clad laminate, is slightly inferior to that of the film material (102 MPa) of Comparative Example 1. Although the tensile strength of the films of Examples 3 and 6 (at the level of 80 MPa) is lower than that of the comparative example, Example 5 (99 MPa) is basically maintained at the same level as that of the film material (100 MPa) of Comparative Example 2, the tensile strength of the polyarylether nitrile-based film materials for flexible copper-clad laminates of Examples 1, 2, and 4 (all exceeding 100 MPa) is significantly improved compared to Comparative Example 2, among which the tensile strength of the film of Example 1 is the best at 112 MPa, followed by Example 4 and Example 2 at 103 MPa and 101 MPa, respectively.
[0103] In summary, the poly(arylether nitrile)-based film material for flexible copper-clad laminates is prepared by the scheme of the present invention. When the polytetrafluoroethylene powder has a particle size of 1 to 15 microns and the mass of polytetrafluoroethylene added in the step of preparing the poly(arylether nitrile) / polytetrafluoroethylene composite film accounts for 5 to 15% of the poly(arylether nitrile) (Examples 1, 2, 4, and 5), the poly(arylether nitrile) / polytetrafluoroethylene composite film and the poly(arylether nitrile) / silicon dioxide composite film can be used through the sandwich structure of the present invention to synergistically solve the problem of decreased tensile strength of the poly(arylether nitrile) film material for flexible copper-clad laminates after adding silicon dioxide for compounding. Furthermore, when the polytetrafluoroethylene powder has a particle size of 1 micron and the mass of polytetrafluoroethylene added in the preparation of the poly(arylether nitrile) / polytetrafluoroethylene composite film accounts for 5% of the poly(arylether nitrile) (Example 1), the tensile strength of the film can be significantly improved.
[0104] The principle analysis is as follows: the addition of polytetrafluoroethylene powder maintains or improves the tensile strength of the polyarylethernitrile film material for flexible copper clad laminates to a certain extent, and plays an important role in the performance stability of the later applications of flexible copper clad laminates. The selection of polytetrafluoroethylene particle size is crucial to its dispersibility in polyarylethernitrile resin, which directly affects the mechanical properties of the film.
[0105] In summary, although Examples 1 to 6 all have a significant improvement effect on the dielectric properties, only Examples 1, 2, 4, and 5 have the effect of maintaining or even improving the tensile strength; further combining the results of other performance measurements, Examples 1 and 4 are preferred preparation schemes, among which Example 1 is more preferred.
[0106] The above disclosure is only the preferred embodiment of the present invention, which cannot be used to limit the scope of the present invention. Therefore, equivalent changes made according to the claims of the present invention are still within the scope of the present invention.
Claims
1. A method for preparing a polyarylether nitrile-based film material for a flexible copper-clad laminate, characterized in that: The steps include: Step 1, obtaining poly(arylene ether nitrile) powder; Step 2, using the polyarylether nitrile powder and nano-silicon dioxide to prepare a polyarylether nitrile / silicon dioxide composite film S, and using the polyarylether nitrile powder and polytetrafluoroethylene powder to prepare a polyarylether nitrile / polytetrafluoroethylene composite film P; Step 3, preparing a polyarylether nitrile-based film material for a flexible copper-clad laminate according to the stacking order of S / P / S; Step 2 specifically includes: 2.1) The poly(arylether nitrile) powder and nano-silicon dioxide described in step 1 are added to solvent a and heated to react to obtain a poly(arylether nitrile) mixture hot solution B. 2.2) Take the poly(arylene ether nitrile) powder and polytetrafluoroethylene powder described in step 1 and add them to solvent a for heating reaction to obtain a poly(arylene ether nitrile) mixture hot solution C. 2.3) forming the mixture hot solution B and the mixture hot solution C into films by tape casting to obtain poly(arylene ether nitrile) / silicon dioxide composite film S and poly(arylene ether nitrile) / polytetrafluoroethylene composite film P, respectively; In step 2.2, the mass percentage of the polytetrafluoroethylene powder to the poly(arylene ether nitrile) powder is 5% to 15%, and the particle size of the polytetrafluoroethylene powder is 1 to 15 microns.
2. The preparation method according to claim 1, characterized in that: Step 3 specifically includes: taking the polyarylether nitrile / silicon dioxide composite film S and the polyarylether nitrile / polytetrafluoroethylene composite film P described in step 2, stacking them in the order of S / P / S, copper-coating them on both sides, and hot pressing them to obtain a flexible copper-clad laminate, wherein the dielectric layer in the middle of the flexible copper-clad laminate is the polyarylether nitrile-based film material for the flexible copper-clad laminate.
3. The preparation method according to claim 1, characterized in that: In step 2.1, the mass percentage of the nano-silicon dioxide in the poly(arylene ether nitrile) powder is 20%, and the particle size of the nano-silicon dioxide is 300 nm.
4. The preparation method according to claim 1, characterized in that: In step 2.1 or step 2.2, the solvent a is N-methylpyrrolidone; in step 2.1, the mass volume ratio of the polyarylethernitrile powder and the N-methylpyrrolidone is 1g:10~15mL; in step 2.2, the mass volume ratio of the polyarylethernitrile powder and the N-methylpyrrolidone is 1g:10~15mL.
5. The preparation method according to claim 1, characterized in that: The reaction temperature of the heating reaction in step 2.1 and step 2.2 is 200°C, the reaction time is 2h, and the heating reaction process is stirred; the heating process of the casting method in step 2.3 includes: the mixture hot solution B and the mixture hot solution C are kept at 80°C, 100°C, 120°C and 160°C for 1h respectively, and then kept at 200°C and 230°C for 2h respectively.
6. The preparation method according to claim 2, characterized in that: The hot pressing temperature in step 3 is 280-320° C., the time is 1 h-3 h, and the pressure is 8-10 MPa.
7. The preparation method according to claim 1, characterized in that: In step 2.2, the mass percentage of the polytetrafluoroethylene powder to the poly(arylene ether nitrile) powder is 5% to 10%, and the particle size of the polytetrafluoroethylene powder is 1 micron.
8. The preparation method according to claim 7, characterized in that: In step 2.2, the mass percentage of the polytetrafluoroethylene powder to the poly(arylene ether nitrile) powder is 5%, and the particle size of the polytetrafluoroethylene powder is 1 micron.
9. A polyarylether nitrile-based film material for a flexible copper-clad laminate, characterized in that: Prepared by the preparation method according to any one of claims 1 to 8.
Citation Information
Patent Citations
Preparation method of high-modulus high-heat-resistance polyarylene ether nitrile self-reinforced film
CN115322417A
Method for molding high-frequency and high-speed acrylic resin copper-cladded plate
CN109517197A
Flame-retardant polyarylether-based composition as well as prepreg and thermosetting high-frequency copper-clad plate prepared from flame-retardant polyarylether-based composition
CN113214630A